2017
DOI: 10.1002/acr.23250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Osteoarthritis on Difficulty Walking: A Population‐Based Study

Abstract: Objective. To assess the relationship of hip and knee osteoarthritis (OA) to walking difficulty. Methods. A population cohort ages ≤55 years recruited from 1996 to 1998 (n = 28,451) completed a standardized questionnaire assessing demographics, health conditions, joint symptoms, and functional limitations, including difficulty walking in the past 3 months. Survey data were linked to health administrative databases; self-report and administrative data were used to identify health conditions. Hip/knee OA was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…Regular exercise is a prerequisite for maintenance and improvement of cardiorespiratory capacity , and walking ability is an important prerequisite for engaging in exercise. However, results from a recent population‐based cohort study showed that hip OA or knee OA is a strong contributor to walking difficulty , and only a small‐to‐moderate proportion of patients with hip OA or knee OA meet the guidelines for physical activity . Many patients with OA spend a considerable amount of time being sedentary, leading to more impairment in physical function, reduced walking speed , and poorer cardiometabolic health compared with their peers who had a less sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular exercise is a prerequisite for maintenance and improvement of cardiorespiratory capacity , and walking ability is an important prerequisite for engaging in exercise. However, results from a recent population‐based cohort study showed that hip OA or knee OA is a strong contributor to walking difficulty , and only a small‐to‐moderate proportion of patients with hip OA or knee OA meet the guidelines for physical activity . Many patients with OA spend a considerable amount of time being sedentary, leading to more impairment in physical function, reduced walking speed , and poorer cardiometabolic health compared with their peers who had a less sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes and Valdes recently reported risk factors shared by both conditions, including age, obesity, chronic inflammation, treatment with nonsteroidal antiinflammatory drugs (NSAIDs), physical inactivity, and walking disability . Patients with hip OA and those with knee OA tend to avoid painful physical activity, resulting in walking disability and physical inactivity , which in turn result in reduced cardiorespiratory fitness. Because cardiorespiratory fitness is an important independent predictor of CVD , OA may be considered to be an indirect cause of CVD .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies carried out in older people have shown considerable ADL problems in these subjects, and have explained that single sensory impairments (either visual or auditory) are significantly and independently linked with a high risk for depression and decreased self‐sufficiency in ADLs, which can adversely affect mobility and the ability to perform ADLs . Furthermore, it seems reasonable to think that the physiological deterioration due to age can be increased or accelerated by the presence of pain that, on many occasions, is due to the musculoskeletal pathology that frequently affects this population …”
Section: Discussionmentioning
confidence: 99%
“…There is therefore a need to devise a cost effective treatment strategy to limit functional decline, joint pain and stiffness. 1 People with osteoarthritis tend to avoid activity due to severe pain, but exercise has proved to be an effective treatment for this condition, reducing pain and improving physical function by improving the strength of the muscles surrounding the knee joint. Twenty-four sessions of therapeutic exercise appear to provide the most bene cial effects, but these effects have not been tested for walking capacity in a 6minute walk test.…”
Section: Introductionmentioning
confidence: 99%